Local wisdom of Mapag Cai tradition of Banceuy villages indigenous community for sociology learning outcomes - Irra Martiana; Dian Peniasiani (Inovasi Kurikulum)
This research aims to apply the value of Gotong royong as local wisdom of Mapag Cai tradition in the Banceuy Village Indigenous Community to be a commodity of wisdom value development in the educational scene of Sociology learning. This research was conducted as an effort to utilize local wisdom so that students understand the meaning of “gotong royong” and strengthen the ties of social interaction in the digital era, which causes indirect interaction that impacts students' interpersonal intelligence. This research uses a descriptive research method that is precise to the characteristics of Mapag Cai social activities. The research was conducted through direct observation and interviewing Banceuy Indigenous Community Leaders, literature studies, and other sources relevant to the writing topic. The results illustrate that the Mapag Cai tradition means the spirit of cooperation and solidarity in maintaining the cleanliness of irrigation channels based on the values and rules held firmly by residents, which can be an inspiration for learning with a contextual approach in building soft skills to foster the spirit of cooperation and social interaction between students.